Acute Effects of Exogenous Hormone Administration on Postprandial Acylation Stimulating Protein Levels in Ovariectomized Rats after a Fat Load. (1st December 2014) - Al Riyami, Bashair; El-Tahir, Marah; Al Maskari, Sultan; Johnson, Eugene H.; Saleh, Jumana
Abstract : Background . ASP, a potent lipogenic factor, was linked to female fat metabolism in association studies. Aim . To investigate acute effects of sex hormone treatment on postprandial ASP levels in vivo . Methods . 24 female rats were randomly divided into 4 groups including controls. The rats were ovariectomized and injected with progesterone, estrogen, or testosterone. An hour later, olive oil was administered orally. Plasma ASP and triglycerides were measured at several postprandial time points. Area under the curve (TG-AUC) represented TG clearance. Results . Only the progesterone treated group had a significant postprandial ASP increase at two hours compared to basal levels (439.8 ± 62.4 versus 253.4 ± 59.03 μ g/mL, P = 0.04 ). Interestingly, increased ASP levels coordinated negatively with corresponding TG levels and TG-AUC postprandially, mostly evident in the opposite effects in the progesterone and testosterone treated groups. ASP levels increased 3-fold in the progesterone versus testosterone treated groups, whereas TG-AUC was significantly lower. Conclusion . These findings suggest that progesterone enhances ASP production and TG clearance simultaneously, supporting the notion of a stimulatory role for progesterone on ASP-mediated TG clearance. This is the first functional study demonstrating a cause-effect relationship between hormone treatment and ASP levels in vivo and may contribute to understanding the mechanism of progesterone function as a female lipogenic hormone.